A Systematic Review of Evidence-Based Alternative Models of Incarceration - Anamalia Suʻesuʻe; Dylan Pilger; Lorinda Riley (Laws)
While much of the American justice system utilizes punitive models of sentencing and incarceration, restorative justice (RJ) approaches provide a holistic alternative to wrongdoing, viewing offenses in terms of relationships and paying particular attention to victim and community needs. These alternative RJ approaches have been shown to decrease recidivism and align with the values of those who have been most impacted by mass incarceration, including Indigenous populations. The purpose of this systematic review is to provide an overview of alternative models of incarceration utilizing RJ principles that could be adapted for a largely Indigenous population.